Status of date palm in Palestine - Abu-Qaoud H. (Le palmier dattier dans l'agriculture d'oasis des pays méditerranéens, 1993)
Palestine has a Mediterranean climate which is characterized by long, hot, dry summers and short, cool, rainy winters. The total area of the West Bank is about 6 million donums (1 donum
Journées Internationales d'Elche sur le Palmier Dattier dans L'Agriculture d'Oasis des Pays Méditerranéens, 25-27 Apr 1995, Elche (Spain)